Diagnóstico do transporte escolar rural público no município de Cachoeiro de Itapemirim-ES - Pinheiro, Theo Goulart Bravo Santos (2013)
It is remarkable the social importance of School Transportation Rural residents of rural areas , as is often the only way to meet the needs of students displacement of residents in these areas to start , continue and finish their studies . Thus , the big problem is presented in this research is being conducted to demonstrate how the school transport in the municipality of Itapemirim under the great number of involved , which makes it vital to know the profile of the users , their needs and thus identify opportunities for improvement . The objective of this work is to diagnose the rural school transport (TER ) in the municipality of Itapemirim - ES by means of school visits and questionnaires to students, parents, educators and school vehicle drivers . We conducted a diagnostic service offered by the Municipality of Itapemirim students of municipal schools , followed by a proposal of actions that allow to improve the conditions of service offered to the students . The results show that most of the students are female , have aged 06-16 years attending elementary school teaching , educators are women and to teach elementary school , and the drivers were males . It was found that students are transported in buses and vans , some being very old , no comfort and no seatbelts for all . It was observed that most students embarks on the doorstep , the foot moves to the point of embarkation , walk 0-05 minutes for a distance 0-500 meters wait 0-05 minutes until the arrival the school bus and spend up to 30 minutes to school . However , there are students who embark on other points , such as highway, walk for 20 minutes, for distances greater than 2 km, waiting for over 20 minutes until the arrival of the school bus and it takes over 60 minutes to get to school. As regards the assessment of the service offered , the survey showed that the people involved are unhappy with some items of service, pointing out that there are many items that need to be improved , especially seating comfort , environmental conditions inside the vehicles , cleaning and state storage of vehicles , which were those which showed more involved unsatisfied. Stakeholders proposed suggestions for improvements , and the purchase of new vehicles the most cited . Finally , at the end of the work have been proposed actions to improve the service provided by an intervention plan.